The impact of COVID-19 pandemic on access to medical services and its consequences on emergency surgery - Pirozzolo, Giovanni; Quoc, Bao Riccardo; Vignotto, Chiara; Baiano, Livio; Piangerelli, Alfredo; Peluso, Claudia; Palumbo, Rubina; Cimino, Fabrizio Giuseppe Maria; Meneghetti, Guido; Grassetto, Alberto; Rizzo, Maurizio; Viola, Gabriele Giuseppe Maria; et al. (Frontiers in Surgery, 2023)
Background On March 9, 2020, the Italian Prime Minister announced the lockdown, which was officially closed on May 4. This extraordinary measure was necessary to contain the COVID-19 pandemic spread in Italy. During this phase, a significant decrease in patients’ access to Emergency Department (ED) was observed. Delayed access to treatment determined a delay in the diagnosis of acute surgical conditions, as already documented in other clinical areas, with consequences on surgical outcome and survival. Aim of this study is to provide a detailed description of abdominal urgent-emergent conditions surgically treated and surgical outcomes during the lockdown in a tertiary referral Italian hospital, compared with historical data. Methods A retrospective review of urgent-emergent patients surgically treated in our department was conducted in order to compare patients’ characteristics and surgical outcomes during the period March 9th - May 4th, 2020 with the same period of the previous year. Results 152 patients were included in our study, 79 patients in 2020 group and 77 patients in 2019. We found no significant differences between the groups regarding ASA score, age, gender, and disease prevalence. Significant differences were found in symptom duration before ER access and abdominal pain as the main symptom in non-traumatic conditions. We also performed a sub-analysis on peritonitis which showed significant differences in: hospital length of stay, presence of colostomy vs ileostomy, and fatal events in 2020. No differences were found in the use of laparoscopy. Conclusions While the overall number of ER accesses has decreased in 2020 group, the number of patients surgically treated in emergency-urgency conditions has not decreased. However, those patients waited significantly more before the hospital access. This diagnostic delay was associated with a more severe clinical condition and a consequent significantly worse prognosis.